Adoption of the Value of Justice in National Food Law - Ahmad Zazili; Mieke Yustia Ayu Ratna Sari; Yatini Yatini (Faculty of Law, Universitas Pekalongan, 2022)
Indonesia is a country that has abundant natural resources; unfortunately, some areas are vulnerable to food insecurity. Such conditions indicate that food development has not reflected justice for the community. This study aims to examine the value of justice in the fulfillment of the right to food. This research applied the statutory approach, the conceptual approach and the philosophical approach. The fulfillment of the right to food for all Indonesians is an obligation of the state, therefore; the values of justice need to be put forward in order to realize national food sovereignty. Social justice is the focus for the direction of development policies to achieve the community welfare. Legal arrangements are needed in the development of food law, such as by drafting laws and regulations in the food sector based on Pancasila values and the constitution, changing the paradigm of food development to food sovereignty, using international legal instruments on food that have a positive impact on people's welfare, and diversifying food as a support for food sovereignty.